1997
DOI: 10.1128/mcb.17.2.895
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor-Glucocorticoid Response Element Binding Stimulates Nucleosome Disruption by the SWI/SNF Complex

Abstract: The organization of DNA in chromatin is involved in repressing basal transcription of a number of inducible genes. Biochemically defined multiprotein complexes such as SWI/SNF (J. Côté, J. Quinn, J. L. Workman, and C. L. Peterson, Science 265:53-60, 1994) and nucleosome remodeling factor (T. Tsukiyama and C. Wu, Cell 83:1011-1020, 1995) disrupt nucleosomes in vitro and are thus candidates for complexes which cause chromatin decondensation during gene induction. In this study we show that the glucocorticoid rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(88 citation statements)
references
References 68 publications
3
84
0
1
Order By: Relevance
“…The GR mutant (R479D/D481R) was created with the Transformer TM site-directed mutagenesis kit (CLONTECH). The GRE-CAT reporter was created by placing a 180-base pair synthetic DNA fragment carrying an appropriately positioned single GRE (20,33) upstream of the coding sequence for CAT. The RB⌬ (1-300) expression plasmid was created by replacing the RB coding sequence upstream of the unique EcoRI restriction site with the codon for methionine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GR mutant (R479D/D481R) was created with the Transformer TM site-directed mutagenesis kit (CLONTECH). The GRE-CAT reporter was created by placing a 180-base pair synthetic DNA fragment carrying an appropriately positioned single GRE (20,33) upstream of the coding sequence for CAT. The RB⌬ (1-300) expression plasmid was created by replacing the RB coding sequence upstream of the unique EcoRI restriction site with the codon for methionine.…”
Section: Methodsmentioning
confidence: 99%
“…In other cases, the SWI/SNF complex is targeted to specific promoters through interactions with DNA-binding components of the transcription machinery. A case in point is GR, a hormone-activated transcription factor that recruits the SWI/SNF complex through direct binding to the hBRM/BRG1 and stimulates nucleosome disruption at the glucocorticoidy response element (GRE) (19,20). Although the remodeling of the chromatin does not influence the ability of GR to access and occupy the GRE, it is essential for post-binding events involving the basic transcription machinery (20) because the TFIID component cannot access the relevant DNA sites until after treatment with glucocorticoid hormone (21).…”
mentioning
confidence: 99%
“…Once GR is bound, it will greatly enhance NF1 and Oct1 binding (Fig. 7), presumably by chromatin opening via recruitment of nucleosome remodeling complex(es) (44,45). Hence, our results imply a more interactive cooperation between the DNA binding factors and chromatin, leading to a stepwise development of more activity-prone chromatin states with an ultimate end point of a transcriptional response.…”
Section: The Mechanism Of Nucleosome Positioning Of the Mmtv Ltr: Intmentioning
confidence: 99%
“…The role of ATP-dependent mechanisms such as SWI/SNF, Mi2/NURD, and ISWI (5) in nuclear receptor-mediated regulation has also been demonstrated. Studies using the glucocorticoid receptor on the mouse mammary tumor virus promoter, which has been shown to have positioned nucleosomes (6), have demonstrated a requirement for SWI-SNF complexes and their ligand-induced targeting to the promoter to activate gene expression (7)(8)(9)(10)(11). More recently, it has been demonstrated that glucocorticoid receptor activation induces nucleosome translational positioning on the mouse mammary tumor virus promoter (12).…”
mentioning
confidence: 99%